Time-Efficient Simulation of Free-Space Optical Communication Systems Under Atmospheric Turbulence, Pointing Error, and Angle-of-Arrival Fluctuations - Mat T. Nguyen; Vuong Mai; Hoon Kim (IEEE Photonics Journal, 2023)
Computer simulation is a powerful and convenient tool for the design and performance evaluation of free-space optical (FSO) communication systems. In this article, we present two simulation frameworks that incorporate not only the effects of atmospheric turbulence but also the impact of the angular fluctuations of the transmitter and receiver in FSO systems. In the first framework, the waveform of the optical signal is calculated sequentially from the transmitter to the receiver. Thus, it takes very long to run the simulation numerous times to obtain the statistical performance of the system. This is because the vast majority of simulation time is spent on the split-step beam propagation. In the second framework, we propose to isolate the beam propagation through atmospheric channel from the other effects. We compare the two frameworks in terms of accuracy and simulation time. We show that the second framework reduces the simulation time by more than a factor of 10 without sacrificing the accuracy under various conditions.